11
1/2 x 6/11 = 6/22 =3/11
(4) divided by (2/3) times (6/11) = (4) times (3/2) times (6/11) = (4 times 3 times 6) / (2 times 11) = 72 / 22 = 3.2727 (repeating)
You get the sum of 11 two ways; 5,6 and 6,5.
(5/7) x (6/11) = 30/77
Six times.
1/6 x 6/11 = 6/66 = 1/11
11 times with six wins.
6•b-11
5x5-36= -11
It's 2.5
11
8/9 x 6/11 x 11/20 is 0.266667
1/2 x 6/11 = 6/22 =3/11
(4) divided by (2/3) times (6/11) = (4) times (3/2) times (6/11) = (4 times 3 times 6) / (2 times 11) = 72 / 22 = 3.2727 (repeating)
19/3 x 11/6 = 209/18 or 11 and 11/18
Oh, dude, that's like basic math. So, 66 divided by 11 equals 6. So, 11 goes into 66 six times. It's like, math 101, man!